Crescimento de oito espécies madeireiras sob duas condições de plantio: a pleno sol e sob dossel da restauração florestal - José, Marina Pérola Zerbinato (2023)
The planting of native timber species is a growing economic activity and a pertinent question, still not clarified, is the best moment to insert timber trees in forest restoration. These species are generally late secondary and shade tolerant, but can respond positively in growth to greater light availability. The objective of this research was to test the hypothesis that the initial growth of native timber species is faster when they are planted in full sun than when planted under a structured forest canopy. We evaluated the relative growth in height and diameter at ground level, and mortality of eight native species of the Atlantic Rainforest, at 12 and 19 months after planting, inserted in two different conditions and moments: in full sun, concomitantly with the pioneer species of the restoration, and under natural shading, in the understory of a forest restoration planting with structured canopy. It was also investigated, only in the shaded planting, whether the seedlings growth is related to the variation in light and vapor pressure deficit levels (VPD) on them. In general, the seedlings from planting in full sun showed higher growth and similar mortality to the seedlings in the shaded plantation, but both presented high levels of mortality. No effect of light and VPD variation was found on tree community growth, possibly due to the punctual way, in space and time, of data collection on temperature, relative air humidity and luminosity in the understory, which seems to not be effective for this purpose. However, at population level, seven of the eight species had significant responses to variations in light and DPV in the area, at some point. The results indicate that it is better to plant timber species in open areas, concomitantly with forest restoration pioneer species, when the objective is the rapid growth of arboreal individuals. To investigate the effect of varying light and VPD on the growth of a community of native timber species, different methods should be tested, such as hemispherical photos or data collections with prolonged exposures, using data-logger sensors. Future studies should evaluate seedlings planted in these different conditions, at more advanced ages, to understand the causes of high general mortality and evaluate the continuity of growth over time, in addition to investigating the architecture of tree individuals and the effect of rapid growth on the wood density, which are important factors for trees planted for the purpose of producing wood destined for sawmills.